Assessment of different storage methods on postharvest quality and shelf life of Darjeeling and Chinese mandarins (Citrus reticulata L.) - Fahim, Md. Abdul; Hassan, Md. Kamrul; Akhther, Nasrin; Howlader, Nayan Chandra; Sarker, Shuvro; Hossain, Md. Sazzad; Ullah, Md. Arman; Akther, Subrina; Rokon, Arafath Hossain (Journal of Plant Stress Physiology, 2025)
Oranges are highly susceptible to postharvest losses due to improper handling and unsuitable storage practices. To address this problem, an experiment was conducted in December 2023 at the Postgraduate Laboratory, Department of Horticulture, Bangladesh Agricultural University, Mymensingh, with the objective of identifying effective methods to extend shelf life and reduce postharvest losses. The study followed a completely randomized design (CRD) with three replications, using two orange varieties: Darjeeling mandarin (V1) and Chinese mandarin (V2). Six treatments were applied: T1 (control), T2 (sealed in 50 μ PP bag without perforation), T3 (sealed in 50 μ PP bag with perforation), T4 (hot water treatment at 50 ± 1 °C for 5 minutes), T5 (sealed in 50 μ PP bag and stored at 6 °C), and T6 (stored at 6 °C without PP bag). The shortest shelf life (12 days) was recorded in Darjeeling mandarins stored in non-perforated PP bags under ambient conditions, while the longest shelf life (47 days) was observed in Chinese mandarins stored in PP bags at 6 °C. This treatment also ensured superior fruit quality in terms of color, firmness, flavor, texture, appearance, minimal shrinkage, and disease-free condition up to 32 days. Furthermore, the lowest weight loss (2.88% at 26 days) and minimal Vitamin C degradation (58.31% at 36 days) were also obtained under this treatment. In contrast, the highest weight loss (68.44%) occurred in fruits stored at 6 °C without PP bags, while the greatest Vitamin C loss (80.17%) was found in hot water–treated fruits stored at ambient conditions. The maximum TSS content (11.66%) was recorded in fruits stored at 6 °C without PP bags, whereas the lowest (6.90%) was observed in fruits sealed in non-perforated PP bags at ambient conditions. In conclusion, packaging mandarins in 50 μ PP bags and storing them at 6 °C proved to be the most effective method for prolonging shelf life and maintaining postharvest quality.